2023
DOI: 10.1371/journal.pgph.0001702
|View full text |Cite
|
Sign up to set email alerts
|

Pre-labor rupture of membranes and associated factors among pregnant women admitted to the maternity ward, Northwest Ethiopia

Abstract: Pre-labor rupture of membranes (PROM) is the rupture of fetal membranes before the onset of labor. PROM is found in 3–15% of all pregnancies and 30–40% of preterm labor worldwide. The most serious complications are neonatal and prenatal mortality, which is higher in Africa, including Ethiopia. Despite a paucity of evidence on the magnitude and factors affecting PROM after 28 weeks of gestation but before the onset of labor (including both term and preterm PROM). Hence, the purpose of this study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Given that variable gestational age was obtained in this study's bivariate analysis with chi squares test and had a p-value of 0.022 α< (0.05), it is possible to draw the conclusion that there is a significant correlation between gestational age and the likelihood of an early rupture of membranes in preterm pregnancy. This is consistent with the research conducted by Takele et al [26] the results of the multivariate analysis showed an AOR: 3.28 (95% CI: 1.53, 7.02), meaning that pregnant women under 37 weeks had a 3.28-fold increased risk of PROM compared to those between 37 and 40 weeks. This research supports the findings of Diriba et al study, which found a correlation between the mother's gestational age and the likelihood of an early membrane rupture with a p-value of 0.018<α (0.05) [16].…”
supporting
confidence: 92%
“…Given that variable gestational age was obtained in this study's bivariate analysis with chi squares test and had a p-value of 0.022 α< (0.05), it is possible to draw the conclusion that there is a significant correlation between gestational age and the likelihood of an early rupture of membranes in preterm pregnancy. This is consistent with the research conducted by Takele et al [26] the results of the multivariate analysis showed an AOR: 3.28 (95% CI: 1.53, 7.02), meaning that pregnant women under 37 weeks had a 3.28-fold increased risk of PROM compared to those between 37 and 40 weeks. This research supports the findings of Diriba et al study, which found a correlation between the mother's gestational age and the likelihood of an early membrane rupture with a p-value of 0.018<α (0.05) [16].…”
supporting
confidence: 92%
“…Khanduri et al suggested that a rise in AFI is the earliest and the most sensitive predictor for GDM [48], a finding that may eventually lead us to conclude that new targeted fasting glucose levels in GDM patients with EGWG should be sought out. The significant differences in PROM prevalence in the EGWG group is most probably related to the AFI rise as well [49].…”
Section: Discussionmentioning
confidence: 92%
“…Pre-labor rupture of membranes (PROM), preceding the onset of labor, occurs in about 2–3% of pregnancies and is a precursor to many preterm births [ 1 ]. Globally, PROM is identified as a leading contributor to preterm births [ 2 ], and its consequences can be severe, including intra-amniotic infection, fetal distress, neonatal sepsis, and heightened perinatal mortality and morbidity [ 3 , 4 ]. The prevailing hypothesis in the recent literature suggests that the genesis of PROM is multifactorial, with environmental air pollution emerging as a notable variable of concern [ 5 ].…”
Section: Introductionmentioning
confidence: 99%